The Role of Customer Satisfaction in Mediating the Effect of Service Claim and Brand Image on Customer Loyalty at PT Asuransi Sahabat Artha Proteksi in Jakarta - Felisia NG; Melitina Tecoalu; Soegeng Wahyoedi (Britain International for Academic Research (BIAR) Publisher, 2022)
The purpose of this study was to determine the role of customer satisfaction in mediating the effect of Service Claim and Brand Image on Customer Loyalty at PT Asuransi Sahabat Artha Proteski in Jakarta. This research was conducted using the Probability Sampling method with the type of Simple Random Sampling. Researchers distributed questionnaires to 100 respondents who were customers of PT Asuransi Sahabat Artha Proteksi in Jakarta. Data analysis using SmartPLS Analysis version 3.3. The results of this study indicate that service claims have a positive and significant effect on customer loyalty. Brand image has a positive and significant influence on customer loyalty. Service claims have a positive and significant effect on customer satisfaction. Brand image has a positive and significant influence on customer satisfaction. Customer satisfaction has a positive and significant influence on customer loyalty. Customer satisfaction mediates the effect of service claims on customer loyalty. Customer satisfaction mediates the effect of brand image on customer loyalty.